Software for partitioning and protecting a water supply network. Issue 1 (2nd January 2016) - Di Nardo, A.; Di Natale, M.; Musmarra, D.; Santonastaso, G.F.; Tuccinardi, F.P.; Zaccone, G.
ABSTRACT: Water network partitioning (WNP) concerns the implementation of the paradigm of 'divide and conquer' in the water supply systems consisting in dividing a water network into k smaller subsystems by gate valves and flow meters. WNP allows improving the management of water distribution systems by transforming into Smart WAter Networks (SWANs) that represent key subsystems of Smart Cities. WNP is possible if water utilities start to use isolating valves (also with control devices) and flow meters. These instruments open new perspectives for the management of water supply systems both in terms of water saving and water protection. Recently, starting from the advantages offered by computing power and network analysis tools, some techniques based on graph partitioning algorithms have been developed by the authors to improve water management and protection, implementing the paradigm of 'divide and conquer'. This paper presents the second release of SWANP 2.0 (Smart WAter Network Partitioning and Protection) software that integrates two different algorithms, based on multilevel and multi-agent techniques, for WNP and a novel algorithm, based on a multi-objective function, for water network protection from intentional contamination. The SWANP 2.0 software, developed in Python v2.7.6 language, provides the decision-maker different solutions comparing network layouts with some hydraulic and protection performance indices.